Reason and racionalities, truth and its posible posmodern versions - Rojas Quispe, Christopher Dante (2019)
The inactivity of a traditional and modern reason in the contemporary world leads us to question the old limits from which the truth was delimited. Then, the decline of a modern reason will be reflected from the effects of truth or its construction through the posmodern lens. Issues such as the arbitrariness of a wholesome reason that still moves its tentacles over diverse areas of thinking, even though rationalities gain more access, will be excuse to reflect, thus, a multidiciplinary entry will be the approach more suitable to reach the objectives of this article.